RISK ASSESSMENT OF FUEL OIL BUNKERING OPERATIONS USING AN INTEGRATED HIRARC–HAZOP FRAMEWORK: A CASE STUDY AT A MARINE JETTY TERMINAL - Bintang Ariesta Sigit Nugraha; Abdul Muid (RADJA PUBLIKA, 2026)
Integrated Terminal Makassar's fuel oil bunkering operations at Jetty 1 and Jetty 2 present significant, intertwined occupational and process hazards. This study analyzed these risks by integrating Hazard Identification, Risk Assessment, and Risk Control (HIRARC) with Hazard and Operability (HAZOP) studies, a novel approach for conventional fuel bunkering. HIRARC identified nine hazards across preparation, transfer, and completion stages, initially rated as low risk, subsequently reduced to low or very low via predominantly administrative controls. HAZOP analysis revealed deeper process deviations underlying these occupational hazards, including communication failures, excessive pressure and flow rates, hose integrity degradation, slippery deck conditions, and inadequate residual fuel handling during completion. The integrated HIRARC-HAZOP framework demonstrates that occupational risks directly correlate with process deviations, a connection often overlooked by single-method analyses. While existing controls are functional, three critical areas require reinforcement: formalizing pre-transfer communication checklists, establishing hose integrity documentation beyond visual inspection, and procedurally mandating the draining and disconnection sequence at operational completion. These refinements aim to enhance safety by moving beyond reliance on spontaneous compliance towards a robust, procedurally driven safety management system.